Risk factors for adolescent pregnancy inBogotá, Colombia, 2010: a case-control study (2014)
Objective. To identify risk factors for adolescent pregnancy among female students in Bogotá, Colombia. Methods. This was a retrospective study of cases and controls matched by age, identified by means of a survey on the sexual behavior of adolescent students in Bogotá (Encuesta sobre el Comportamiento Sexual de los Adolescentes Escolarizados en Bogotá) conducted in the first semester of 2010. All 272 cases and 544 randomly-selected controls were taken from 39 044 total records. Variables considered were sociodemographics, household structure, and family environment; sexual relationships and pregnancy; and knowledge of sexual and reproductive health. Matching and conditional logistic regression were used to adjust for possible confounding factors. Results. The factors associated with increased risk of adolescent pregnancy based on multivariate analyses were: attending public school (odds ratio [OR] = 2.25; 95% confidence interval [95% CI]: 1.45–3.51); history of siblings with adolescent pregnancy (OR = 1.98; 95% CI: 1.55–2.76); early first sexual intercourse (12 years of age or less) (OR = 2.34; 95% CI: 1.01–5.40); having a self-reported low- or average-level of contraceptive knowledge (OR = 3.92; 95% CI: 1.96–7.83); previous pregnancy (OR = 14.09; 95% CI: 8.74– 22.70); and not living with both parents (OR 3.58; 95% CI: 2.10–6.16). Conclusions. Factors related to individual, family, and social environments that influence the incidence of adolescent pregnancy must be considered and addressed when designing interventions. The existing sex education curriculum is an important component in preventing adolescent pregnancy, however, parent/caregiver participation is required for success.